Identification of volatile components and analysis of aroma characteristics of Jiangxi Congou black tea - Cuinan Yue; Puxiang Yang; Dandan Qin; Hailan Cai; Zhihui Wang; Chen Li; Hualing Wu (International Journal of Food Properties, 2020)
Jiangxi Congou black tea is one of the earliest Congou black tea in China. In order to explore its sensory characteristics and molecular sensory basis, quantitative description analysis (QDA) and gas chromatography-mass spectrometry (GC-MS) were used to analyze the sensory characteristics and volatile components of 11 Congou black tea samples from Jiangxi Province in China. The results showed that the aroma characteristics of Jiangxi Congou black were composed of 11 aroma descriptors, namely, sweet-smell, floral, fruity, roasted, spicy, fresh, green, oil, off-odor, woody and smoky. There was also interaction effect between sensory attributes of aroma, which were significant negative correlation between floral, and fruity, and green. The presence of roasted incense could significantly enhance the olfactory perception of off-odor and smoky, and off-odor was an important attribute that affects the aroma quality of Jiangxi Congou black tea. Volatile components (i.e. 74 kinds) were identified, among which the highest content and species were alcohols, followed by esters, and the lowest were heterocycles and terpenes. The results of partial least square variable import project (PLS-VIP) showed that there were 29 volatile compounds that had an important contribution to the aroma characteristics of Congou black tea, and the volatile compounds that had an important influence on six aroma attributes were obtained.